Will reducing border barriers via the EU's b-solutions lead towards greater European territorial integration? - Medeiros, E.; Ramírez, M. G.; Dellagiacoma, C.; Brustia, B. (Regional Studies, 2022)
Despite the positive contributions of several European Union (EU) policies to reduce border barriers, the EU Cross-Border Review (CBR) initiative reaffirmed their relevance and persistence. Since 2018, the EU has supported the b-solutions initiative, specifically focused on tackling legal and administrative border obstacles, aiming to highlight replicable solutions which can contribute to reducing these obstacles. This article critically assesses the b-solutions and its contribution to reducing administrative and legal border obstacles, with an eye to promoting a more integrated European territory. It is concluded that b-solutions is a valid, yet insufficient, initiative to provide replicable solutions to mitigate cross-border barriers.